Neonatal appendicitis with perforation: A case report and review of literature - Gupta Vipul; Sharma S (Wolters Kluwer Medknow Publications, 2005)
Acute perforated appendicitis is described as a rare clinical entity in 20 days old male neonate presented clinically with features suggestive of peritonitis. Surgical exploration revealed perforated appendix with free fluid in peritoneal cavity. Appendectomy with general supportive measures resulted in a satisfactory recovery. Authors review their experience with this rare entity along with pertinent literature.